A splice variant of ADAMTS13 is expressed in human hepatic stellate cells and cancerous tissues - Shomron, Noam; Hamasaki-Katagiri, Nobuko; Hunt, Ryan; Hershko, Klilah; Pommier, Elie; Geetha, S.; Blaisdell, Adam; Marple, Andrew; Roma, Isabella; Newell, Jordan; Allen, Courtni; Friedman, Scott; Kimchi-Sarfaty, Chava (Thrombosis and Haemostasis, 2010)
Although ADAMTS13, the von Willebrand factor (VWF)-cleaving protease, is expressed in a range of tissues, the physiological significance of tissue-specific ADAMTS13 alternative splicing isoforms have yet to be clarified. Screening a panel of human tissues and cell lines revealed a spliced ADAMTS13 transcript in hepatic stellate cells and a hepatoma cell line that retains the 25th intron. A nonsense codon within the intron truncates the protease, which gains 64 novel amino acids in lieu of both CUB domains. This isoform, while retaining VWF-cleaving capability, accumulates intracellularly and its biological inaccessibility may prevent its participation in regulating haemostasis and other physiologic functions.
Keywords: ADAMTS13; alternative splicing; intron retention; TTP; CUB domain